Avaliação Psicossociológica em Idosos Institucionalizados - Luna, Karínthea Kerlla Gonçalves Pereira (2009)
The aging process of human beings the world has become an important and disturbing event from the economic, biological, psychological and social that has attracted attention of scholars of the subject, reflecting on the conditions of concern to subsidize the promotion of quality of life of this group in different areas of knowledge. This study has the objective of evaluating depression in the institutionalized elderly, measure the quality of life in elderly, finds the association between depression and quality of life in institutionalized elderly with emphasis on socio-demographic characteristics and apprehend the social representations of 'being old' and 'be institutionalized elderly, emphasizing the psychosocial aspects. This is an exploratory and descriptive epidemiological study, conducted in similar socio-cultural contexts, which prioritized the speech of subjects and experiences, subsidized the theoretical contribution of social representations in a quantity - qualitative approach capable of meeting the proposed objectives. The study was conducted in four institutions which house the elderly, in the great João Pessoa, Paraíba, Brazil. Study participants were seventy elderly, aged 60 to 98 years, both sexes. To collect data using the multi-technique approach including tools: Depression Scale Geriatric abbreviated Geriatric Depression Scale (GDS), WHOQOL Bref, WHOQOL-OLD and a semi-structured interview. The data were statistically analyzed perceived and interpreted in light of the theory of social representations. The results of the depression indicate the following assessment: 3.7% were normal, 77.2% with mild depression and a percentage of 17.1% with severe depression. With regard to the quality of life reported by the institutionalized elderly, it is observed that 55.7% (39) consider the quality of life "Good," while 44.3% is for "Bad". It was observed with respect to the health of the elderly there was a small predominance with satisfactory statement: 52.9%, while 47.1% were dissatisfied the elderly studied. The test of significance for the linear correlation coefficient r of Pearson between measures of general issues of the WHOQOL-Bref provided results: N = 70, r = 0401 with p-value = 0001 (significant at 1%), indicating correlation significant positive linear: quality of life of older people and satisfaction with health. The diseases most frequently mentioned by the elderly are hypertension and diabetes. The elderly represent a person "old" from a position adverse to the same result for the elderly institutionalized. They feel abandoned and senior associate to 'death' and 'abandonment'. To investigate the psychosocial aspects of the institutionalized elderly is a possibility of knowing how they are positioned opposite to themselves, as they are facing a reality often ignored by societies which participate.